PENYULUHAN HIV/AIDS TERHADAP KALANGAN REMAJA, MASYARAKAT BR. NYAMPING, DESA GUNAKSA, KECAMATAN DAWAN, KABUPATEN KLUNGKUNG - Wardani, Agung Cahaya; Sumadiyasa, I Kadek; Indriani, Made Novia; Putri, Ni Putu Rika Loistiana; Pradnyana, I Wayan Ferry Surya; Juliantari, Ni Komang (UNHI Press, 2025)
The immune system can become infected by the virus known as HIV (Human Immunodeficiency Virus). This viral infection is able to weaken the ability of human immunity to fight foreign objects in the body, which in the terminal stage or severe infection can cause Acquired Immunodeficiency Syndrome (AIDS). HIV is a virus that harms the body's lymphocytes, or white blood cells, and lowers the immune system. This work program aims to prevent transmission of the HIV virus in the Gunaksa Village community and in general. The method for implementing this HIV/AIDS socialization work program is to coordinate with the Dawan II Community Health Center UPTD as a health facility in the Gunaksa Village area, carrying out direct outreach activities to POSBINDU and Youth Posyandu participants in an interactive and communicative manner to the community of Br. Nyamping and Gunaksa Villages in general regarding HIV/AIDS, along with the implementation of the POSBINDU and Youth Posyandu programs, participate in contributing to health examination services to the community, such as checking body weight (BB), height (TB), blood sugar and blood pressure and health mentally guided directly by the UPTD of the Dawan II Community Health Center.